Notes on Dysderidae (Arachnida, Araneae) of Armenia and Iran, with new species and records - Kosyan Armine; Zamani Alireza; Marusik Yuri M. (Pensoft Publishers, 2025)
New data are provided on dysderid spiders of Armenia and Iran. Dysdera haykana sp. nov. is described based on male specimens collected in Kotayk and Lor provinces, central and northern Armenia. The female of Dysdera nakhchivanica Beydizade, Shafaie & Guseinov, 2018 is described for the first time, and the species is newly recorded from Armenia. Furthermore, new distribution data are provided for Harpactea armenica Dunin, 1989, including the first record of the species from Iran. Photographs and a distribution map are provided for all three species.